Wilms tumour in children: 18 years of experience at Vilnius University Hospital Santaros Klinikos, Lithuania - Rančelytė, Milda; Nemanienė, Rolanda; Ragelienė, Lina; Rascon, Jelena (Acta medica Lituanica, 2019)
Introduction. Wilms tumour (WT) is the most common childhood abdominal malignancy, with an average annual incidence of 1 in 10,000 children. The study published in 2002 reported lower survival rates of WT in Lithuania in comparison to the data of SIOP-9 study and the European Organization for Research and Treatment of Cancer (EORTC). We aimed to assess current diagnostic approach and treatment results of patients with WT treated at our institution and to compare the results with the previously published study. Materials and methods. A retrospective single-centre study was performed. 48 patients with WT registered at the institutional database from 2000 to 2018 were enrolled. An estimated 5-year overall survival (OS5y) and 2-year event-free survival (EFS2y) by stage and risk groups was calculated using IBM SPSS. A comparative analysis of two time periods – 2000–2008 and 2009–2018 – was carried out. Results. Forty-two (87.5%) patients presented with localised disease and 6 (12.5%) with primary metastatic disease. The majority of cases were of the intermediate-risk group (77%). The OS5yof all analysed children was 86.4%. The EFS2y was 88.9% in stage I, 91.7% in stage II, 83.3% in stage III, and 50% in stage IV. The EFS2y was 100% in the low-risk group, 86.5% in the intermediate-risk group, and 25% in the high-risk group. Improvement of outcomes was observed over the analysed period: OS5y changed from 81.0% in 2000– 2008 to 92.6% in 2009–2018. Among 48 cases, ten patients showed recurrence: eight – early relapse and two – late relapse. Six patients died. Conclusions. WT was diagnosed at early stages in most cases. The survival was better among the patients diagnosed in earlier stages and with favourable risk group. Better survival rates were observed in patients treated in 2009–2018 compared to the 2000–2008 period.